PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN 03 KOTO BARU - dedi, Aprima; Filahanasari , eka; Purmala Sari, Elvi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the suboptimal state of Indonesian language learning, low student interest in writing, and students' inability to express ideas or thoughts in written form. This situation is further evidenced by Mid-Semester Assessment (PTS) scores that remain unsatisfactory, with many students scoring below the Minimum Completeness Criteria (KKM). To address this issue, the researcher conducted a study utilizing the Flipped Classroom learning model. This study aims to determine the effect of the Flipped Classroom model on the topic "The Natural Beauty of My Village" in the Indonesian language subject. This study employed a Pre-Experimental Design, specifically the One-Group Pretest-Posttest Design. The research was conducted at UPT SDN 03 Koto Baru during the even semester of the 2025/2026 academic year, with a sample consisting of 21 fourth-grade students. Data collection instruments included learning outcome tests (multiple-choice and essays) administered through pretests and posttests. Based on the paired sample t-test results, a significance value of $0.000 < 0.05$ was obtained. Consequently, it can be concluded that the Flipped Classroom learning model has a positive and significant effect on the Indonesian language learning outcomes of fourth-grade students at UPT SDN 03 Koto Baru. Independent learning activities at home proved optimal in saving time, allowing classroom activities to focus on strengthening literacy skills interactively.